ArgoSpine News & Journal - Mazel, Christian; Kehr, Pierre; SpringerLink (Online service) (Paris : Springer Paris : Imprint: Springer.)
Argos Association (now ArgoSpine Association) was created in 1996 by gathering each year the surgeons specialised in spine, as well orthopaedists and neurosurgeons, on a two-day symposium. Other specialists of the spine joined them: radiologists, neurologists, anatomists, but also engineers and biomechanicians. Right from the start, Argos aimed to prolong its activity of teaching and training through the medium of its journal. It initially was published twice a year and is now at a frequency of 4 issues per year. The aim of the ArgoSpine Association and Springer is to accompany the evolution of the journal to the status of a scientific journal with articles reviewed by a scientific committee and to increase its impact throughout the world. The purpose of our ArgoSpine News and Journal is to continue the way previously defined by developing the topics approached during the annual symposium, by featuring talks with the invited lecturers, but also by publishing issues focusing on specific topics through interviews or articles of outstanding personalities in the field of spine pathology.
Keywords: Radiology; Orthopedics; Orthopedics; Surgical Orthopedics; Diagnostic Radiology